AB0557 Heart lesson in eosinophilic granulomatosis with polyangiitis. (15th June 2017) - Rednic, D; Rancea, R; Cozma, F; Damian, L; Muntean, L; Tamas, MM; Simon, S-P; Felea, I; Rednic, S
Abstract : Background: Eosinophilic granulomatosis with polyangiitis (EGPA) is a disorder characterised by systemic small vessel vasculitis, that occurs typical in patients with a positive history of late-onset asthma and allergic rhinitis. Cardiac involvement is the major cause of mortality. There is required a standardised method to assess cardiac involvement in EGPA. Objectives: To assess the clinical and imagistic caracteristics of EGPA patients with cardiac involvement in a tertiary referral hospital. Methods: Fourteen patients (pts) with EGPA were retrospectively analysed between 2010–2016, in Rheumathology Departament in Cluj-Napoca. All patients were screened for cardiac involvement by electrocardiogram (ECG) and cardiac ultrasonography (CUS). Cardiac involvement was defined as follows: ventricular hypertrophy, kinetic abnormalities, valvulopathy, pericardial effusion or diastolic dysfunction. Cardiac magnetic resonance (CMR) and coronarographie was assessed in 4 pts with ECG or CUS abnormalities. Results: Characteristics of EGPA patients is detailed in table 1 . Six out of 14 pts had cardiac involvement (table 2 ). Only one patient was symptomatic. CMR abnormalities were: endocardial fibrosis in 2 pts, subepicardial inflammation and fibrosis in 1 patient, ventricular hypoperfusion in 2 pts and hypertrophic cardiomyopathy (HCM) in 2 pts. The pts with subepicardial inflamation and HCM had a more severe outcome. Three out of the 6 pts with cardiac involvement were pANCA (+). Hypereosinophilia was singnificantly higher in the group with cardiac involvement (p<0.012). None of the patients had positive coronarography. Conclusions: Cardiac involvement is frecvent and is associated with hypereosinophilia. Absence of pANCA was not associated with the cardiac involvement, in contrast with other publications. CMR makes the difference between inflamatory and noninflamatory lesions, beeing useful in clinical assessment and in treatment decisions, therfore this examination could avoid a fatal outcome. Furthermore, in the future, CMR may replace cardiac byopsy. References: Thomas Neumann Cardiac Involvement in Churg-Strauss Syndrome Impact of Endomyocarditis. Medicine (Baltimore). 2009 Jul;88(4):236–43. Nir Pillar, MD Hypereosinophilic Syndrome With Cardiac Involvement: Early Diagnosis by Cardiac Magnetic Resonance Imaging. Canadian Journal of Cardiology 28 (2012) 515.e11–515.e13. Disclosure of Interest: None declared